MODEL PENGEMBANGAN EKOWISATA DALAM MENDUKUNG KEMANDIRIAN EKONOMI DAERAH STUDI KASUS PROVINSI DIY (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2014)
Along with the development and economic growth processing, the role of tourism nowadays is more essential, as new sectors that contibuting foreign exchange for the improvement of people's welfare. Indonesia is one country that has a many natural and cultural remarkable, also enjoy this benefit. However, tourism is often regarded as one of the largest damage contributor to the preservation of the environment and the community, particularly through the development of the infrastructure. Yogyakarta Province as one of the tourist destinations, also face the same problem, a shift in cultural values, social and environmental wisdom. Ecotourism then regarded as one of the policy alternatives that can be used as a solution to this problem. By using a qualitative approach, this study was conducted with the aim of formulating a model-based sustainable ecotourism cultural values, social and environmental wisdom that will support the successful development of tourism in Yogyakarta. With the development of this policy model, expected to be a guideline for governments in developing national policies in the field of sustainable tourism in order to strengthen the economic independence in the region.